Preliminary Findings on Antibacterial Activity of Selected Marine Invertebrates - Marina Brailo Šćepanović; Jasna Maršić-Lučić; Romana Beloša; Sanja Tomšić (Applied Sciences)
Antibacterial resistance has become a major problem where new promising drugs are needed. The extracts obtained from marine invertebrates Mytilus galloprovincialis, Patella sp., Gibbula sp. and Arbacia lixula were tested against bacteria using the disc diffusion method. Citrobacter sp. from seawater and Paenibacillus sp., Bacillus sp. and Geobacillus sp. from soil were used as well as the reference bacterial strains Staphylococcus aureus NCTC 12981, S. aureus subsp. aureus Rosenbach ATCC 6538, Salmonella enterica subsp. enterica serovar Enteritidis ATCC 13076, Salmonella enterica subsp. enterica serotype Typhimurium NCTC 12023, Listeria monocytogenes ATCC 19111, Klebsiella aerogenes ATCC 13048 and Escherichia coli NCTC 12241. The most successful bacterial inhibitors, inhibiting 8 of 13 strains were extracts of M. galloprovincialis, Patella sp., Gibbula sp., Enteromorpha sp., C. sinuosa and U. lactuca, extract of A. lixula showed antibacterial activity against five bacteria, while extract of C. officinalis showed no antibacterial activity. These results indicate the potential of these marine organisms as a source of antibacterial compounds and may serve as a basis for further research and development of new antibacterial agents.